Catching fairies and the public representation of biogeography - Ladle, R (Blackwell Publishing Ltd., 2008)
Biogeography is a vibrant academic discipline that plays an important role in framing and directing debates on some of the most important environmental issues of our time, such as the impacts of climate change on biodiversity, biotic homogenization and the effectiveness of global conservation policy. Despite this, biogeography suffers from a low public profile and may consequently be poorly understood by the public. Here I review the representation of the term biogeography, and a selection of biogeographers in the public sphere (newspapers, websites, blogs) and the academic sphere (journals and reports) to understand more fully the public perception of the discipline. As anticipated, the survey suggests that the term ‘biogeography’ has little public currency, and that the public still largely associate the subject area with either eminent Victorians such as A.R. Wallace or modern greats such as E.O. Wilson. I conclude by discussing the potential consequences of the virtual absence of biogeography from public discourse for education and professional biogeographers.